The art of teaching children : all I learned from a lifetime in the classroom - Done, Phillip (Avid Reader Press, 2022)
"After more than thirty years in the classroom, award-winning teacher Phil Done decided that it was time to retire. His days of teaching schoolchildren may have come to an end, but a teacher's job is never truly done, and he set out to write the greatest lesson of his career: a book for educators and parents that would pass along everything he learned about working with kids. The result is this delightful and insightful teaching bible, The Art of Teaching Children. From the first-day-of-school jitters to the last day's tears, Done writes about the teacher's craft, classrooms and curriculums, the challenges of the profession, and the reason all teachers do it--the children"--